2008
DOI: 10.1016/j.immuni.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of Mouse Immunoglobulin Kappa Deleting Element Recombining Sequence Promotes Immune Tolerance and Lambda B Cell Production

Abstract: The recombining sequence (RS) of mouse and its human equivalent, the immunoglobulin (Ig) kappa deleting element (IGKDE), are sequences found at the 3' end of the Ig kappa locus (Igk) that rearrange to inactivate Igk in developing B cells. RS recombination correlates with Ig lambda (Iglambda) light (L) chain expression and likely plays a role in receptor editing by eliminating Igk genes encoding autoantibodies. A mouse strain was generated in which the recombination signal of RS was removed, blocking RS-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 54 publications
3
46
0
1
Order By: Relevance
“…This suggests that transitioning or maturing B cells are involved in tolerance induction and/or maintenance; alternatively, these cells may be suppressed by immunosuppression. Studies have shown that mature B cells in transition after antigen stimulation undergo receptor editing as means of promoting tolerance to self antigens (29,30). Although receptor editing is believed to take place centrally in the bone marrow, it is possible that this mechanism is used peripherally in transplant recipients, as also shown in autoimmune models (31).…”
Section: Figurementioning
confidence: 99%
“…This suggests that transitioning or maturing B cells are involved in tolerance induction and/or maintenance; alternatively, these cells may be suppressed by immunosuppression. Studies have shown that mature B cells in transition after antigen stimulation undergo receptor editing as means of promoting tolerance to self antigens (29,30). Although receptor editing is believed to take place centrally in the bone marrow, it is possible that this mechanism is used peripherally in transplant recipients, as also shown in autoimmune models (31).…”
Section: Figurementioning
confidence: 99%
“…The Ig locus undergoes rearrangement next in pre-B cells, where a V gene is joined to a J region. If Ig V-J joining is productively unsuccessful because of out-of-reading frame recombination junctions, then the Ig locus becomes activated for rearrangement and expression, which in wild-type (WT) mice accounts for production of only approximately 5% of the total IgL chains (2).…”
mentioning
confidence: 99%
“…Recombination of Kde with either an upstream V k or an isolated RSS heptamer recombination element (RE) in the J k eC k intron results in the physical deletion of the C k exon and silencing of the k locus [19]. Kde sequences have been identified in mice and humans [20e22] and more recently in the genomes of several additional mammals including the platypus [23].…”
Section: Palindromic Heptamers In Zebrafish C Lmentioning
confidence: 99%